The Museums of Egypt after the 2011 Revolution. Issue 1 (21st June 2016) - Rashed, Mohamed Gamal
Abstract: Not only are Egyptian museums an asset in developing the country's economy, but they also play a pivotal social role in developing community‐based activities and fostering dialogue. This role was emphasised after the 2011 revolution. Although museums in Egypt faced several threats and challenges during and after the revolution, the social change that it brought about highlighted the importance of museums. Museums encounter many opportunities that restore and strengthen their relationship with diverse Egyptian communities. This paper describes and documents the changes happening in Egypt's museums. As forums in which social matters can be discussed, museums play a foremost part in the promotion of social change and development. This is particularly true of museums in countries that have seen the rise and fall of great ancient civilisations, such as Egypt.